2018
DOI: 10.1093/nutrit/nuy017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whey protein supplementation on body composition changes in women: a systematic review and meta-analysis

Abstract: Whey protein supplementation improves body composition by modestly increasing lean mass without influencing changes in fat mass. Body composition improvements from WP are more robust when combined with ER .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…Meta-analyses from controlled clinical trials predominantly in men have suggested a synergistic effect of resistance training and protein supplementation [16,37,38]. Interestingly, studies investigating the effect of protein supplementation and resistance exercise in women, and in particular on non-athletic premenopausal women, are scarce [26]. Most studies in women have been performed with postmenopausal women, some of them investigating the effects of different exercise regimens, others studying the influence of different nutrients including protein [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analyses from controlled clinical trials predominantly in men have suggested a synergistic effect of resistance training and protein supplementation [16,37,38]. Interestingly, studies investigating the effect of protein supplementation and resistance exercise in women, and in particular on non-athletic premenopausal women, are scarce [26]. Most studies in women have been performed with postmenopausal women, some of them investigating the effects of different exercise regimens, others studying the influence of different nutrients including protein [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects on fat or muscle mass were rather small. In a current systematic review and meta-analysis, it was revealed that the effect of whey protein supplementation on fat free mass in young and old women in combination with a resistance training were +0.23 kg [26]. However, the calculation included both female athletes and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to exceed the anabolic threshold, fast proteins which increase more the aminoacidemia are specifically of interest. It is well-known that lactoserum proteins are fast proteins (Boirie et al, 1997;Dangin et al, 2003); they are rich in leucine and trigger more the protein synthesis than casein and are more efficiency in order to limit the muscle protein losses in the elderly (Pennings et al, 2011;Bergia et al, 2018). A recent cross-sectional study in women older than 65 years confirms that the animal protein intakes, and particularly the dairy protein intakes are correlated to the bone strength microstructure (Durosier-Izart et al, 2017).…”
Section: Energy and Protein Requirementsmentioning
confidence: 96%
“…Whilst not reporting change in body weight these outcomes were accompanied by a decrease in waist circumference, which is an indirect measure of central adiposity expected to also be accompanied by weight loss. Whey protein has long been shown to have modest positive effects on body composition during weight loss (33), but whether there are effects of whey protein on CV endpoints independent of change of body weight remains to be convincingly demonstrated. Previous observational studies have reported weight independent effects of total protein intake on cardiometabolic health, with authors in turn noting that the role of protein in CV health likely depends on the specific protein source (34).…”
Section: Whey and Caseinmentioning
confidence: 99%